A new ricefish of genus Oryzias (Teleostei: Adrianichthyidae) from western Taiwan - Chen, I-Shiung; Lai, Hong-Thih (Zootaxa, 2024)
The new brackish ricefish were collected recently from western Taiwan which has been identified as the species new to science. The new species, Oryzias chenglongensis n. sp. can be well distinguished from other congeners by the following unique combination of features: (1) fin-ray counts: dorsal-fin rays 6 (6 seen in holotype); anal-fin rays 19–20 (19); pelvic-fin rays 6 (6); pectoral-fin rays 10 (10); principle caudal-fin rays i,4/5,i (i,4/5,i); (2) body compressed laterally with body depth at pelvic origin 24.0–24.3 (24.3), body depth at anal fin origin 15.5–20.4 (20.4); (3) the dorsal-fin origin inserted almost at the vertical of 14th anal-fin rays, membrane between dorsal-fin 5th and 6th rays without distinct notch in adult male; and (4) body translucent, light yellowish green or brown, scattered with minute melanophores, a narrowly dotted, longitudinal black line along the middle forward to vertical above pelvic fin; T-shape black mark of caudal fin base in male; operculum and pre-pectoral region slivery, no any silvery scales on lateral body, lip color grayish or creamy yellow and eye bluish silvery dorsally. The diagnostic characters, and comparison with related species would be also provided.